Tunagrahita Student Learning Expert System with Backward Chaining Method at YKDW 01 Tangerang School - Hidayat, Rachmat; Haryanto, Haryanto; Sapinah, Pipin (Sinkron : jurnal dan penelitian teknik informatika, 2019)
In general, the habit of learning a person is influenced by personality variables. Not a few parents who do not understand about the method of effective learning for children, the parents and teachers must approach first in order to know the personality and habits of children, especially children with a tunagrahita. Learning method given to the child is very important, therefore teaching methods applied by parents at home and given by teachers should be the same in order to facilitate the child in understanding the lesson and not experiencing confusion because accept different learning methods. This is very influential, because there are still many students with disabilities who still have difficulty understanding the learning especially reading, writing and counting where the learning will be very influential for the community. Based on these problems it is necessary expert system to facilitate parents in providing home study in accordance with the methods of learning provided by teachers at school so that students more easily and quickly in understanding the lesson